2015
DOI: 10.1016/j.ssresearch.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Getting support in polarized societies: Income, social networks, and socioeconomic context

Abstract: This paper explores how unequal resources and social and economic polarization affects the size of social networks and their use to access resources. We argue that individual resource position generates divergent expectations with regard to the impact of polarization on the size of networks on one hand, and their usefulness for accessing resources on the other. Social and economic polarization encourages reliance on informal networks, but those at the bottom of the social structure are forced to rely on more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(20 citation statements)
references
References 61 publications
0
19
0
1
Order By: Relevance
“…The European Commission [73] has suggested that efficiency might be complemented or replaced by the notion of sufficiency. Deciding upon the size and character of social and environmental thresholds and determining sufficiency criteria are understood to require inputs from actors outside of firms as units of production [65,74].…”
Section: Proposed Sbmcc Measuresmentioning
confidence: 99%
“…The European Commission [73] has suggested that efficiency might be complemented or replaced by the notion of sufficiency. Deciding upon the size and character of social and environmental thresholds and determining sufficiency criteria are understood to require inputs from actors outside of firms as units of production [65,74].…”
Section: Proposed Sbmcc Measuresmentioning
confidence: 99%
“…Having a more extensive support network in adolescence implies having a resource that protects various aspects of health [ 60 ]. Difficulties in forming ties can be compounded by SES: individuals with few resources in the social structure are disadvantaged by their dependence on larger networks to access social resources [ 61 ], and in turn, the configuration of social networks is conditioned by socioeconomic status. Although networks vary over the course of life according to SES [ 62 ], the presence of these deficits at an early age restricts subsequent possibilities for improvement, thus contributing to greater inequality.…”
Section: Discussionmentioning
confidence: 99%
“…These two measures can sometimes give contradictory results, for example, it has been shown that occupational groups like managers are members of a larger number of organisations, but spend less time participating (Fisher et al 2004). Membership is also not necessarily related to larger networks (Letki and Mierina 2014). One should be careful thus when presenting the results based on membership information.…”
Section: Consequences Of the Economic Crisis For Social Capitalmentioning
confidence: 99%